2015
DOI: 10.1160/th14-05-0452
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation and low-molecular-weight heparin prophylaxis in pregnant women with thrombophilia

Abstract: Pregnancy is associated with increased risk of venous thromboembolism, especially in the presence of thrombophilia. However, there is no consensus on the optimal approach for thromboprophylaxis in this population. Recent evidence suggests that thrombin generation correlates with the overall procoagulant state of the plasma. Our aim was to evaluate thrombin generation in a prospective cohort of thrombophilic pregnant women, and investigate the effectiveness of low-molecular-weight heparin (LMWH) prophylaxis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Previously, it was shown that the very course of pregnancy is accompanied by an increase in the haemostatic potential, including thrombin potential [44][45][46][47]. The present work, like the study of Selmeczi A et al, revealed not only a bigger increase in thrombin generation during pregnancy in FVL (1691) GA women (compared to the FVL (1691) GG genotype), but also a decrease in thrombin generation due to heparin prophylaxis [48]. In particular, suppression of thrombin generation by LMWH in comparison to the absence of heparin prophylaxis determined from 22 weeks of gestation, including median and peak thrombin was by 9.0% (p =0.0083) and ETP by 4.0% (p =0.0042).…”
Section: Partsupporting
confidence: 79%
“…Previously, it was shown that the very course of pregnancy is accompanied by an increase in the haemostatic potential, including thrombin potential [44][45][46][47]. The present work, like the study of Selmeczi A et al, revealed not only a bigger increase in thrombin generation during pregnancy in FVL (1691) GA women (compared to the FVL (1691) GG genotype), but also a decrease in thrombin generation due to heparin prophylaxis [48]. In particular, suppression of thrombin generation by LMWH in comparison to the absence of heparin prophylaxis determined from 22 weeks of gestation, including median and peak thrombin was by 9.0% (p =0.0083) and ETP by 4.0% (p =0.0042).…”
Section: Partsupporting
confidence: 79%
“…Both peak thrombin and ETP were increased over the course of pregnancy compared with the nonpregnant state (8 weeks postpartum) in women with mild thrombophilia (women with heterozygosity for FVL or Prothrombin 20120A mutation and/or a positive history for VTE and/or a positive family history for VTE) as well as those with no thrombophilia. 179 On the contrary, other authors demonstrated that the ETP remained unchanged in both women with and without FVL at all time points (12th, 22nd, and 34th gestational weeks as well as 3 months after delivery). 106 Parameters of TEG "r," "k," and TMA increased while α-angle decreased in patients with inherited thrombophilia as compared with controls.…”
Section: Thrombophiliamentioning
confidence: 85%
“…But two parameters of thrombin generation -peak thrombin and endogenous thrombin potential -were higher in pregnant women compared to non-pregnant women, especially in those with severe thrombophilia. The peak of thrombin generation was lower in women who received low molecular weight heparin as prophylaxis, but this effect diminished with the progression of pregnancy [4].…”
Section: The Progression Of Thrombin Generation Parameters In Pregnancymentioning
confidence: 93%
“…The hypercoagulable state of pregnant women is associated with anatomic and physiologic changes that occur during pregnancy [3]. The risk of venous thromboembolism is higher especially in thrombophilic pregnant patients [4] and in females with a low birth weight newborn or stillbirth [3]. The classical assays used to explore the coagulation state are inadequate for estimating the thrombotic risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation